Posterior reversible encephalopathy syndrome in Guillain-Barré syndrome. Issue 5 (May 2015) - Chen, Adam; Kim, Jennifer; Henderson, Galen; Berkowitz, Aaron
Abstract Autonomic dysfunction is a well-known complication of Guillain-Barré syndrome (GBS) and may manifest as hemodynamic fluctuations. Posterior reversible encephalopathy syndrome (PRES) is commonly associated with acute hypertension, but is rarely reported to occur in association with GBS. We describe a patient with GBS who developed PRES in the setting of autonomic dysfunction and review the clinical features of all 12 previously reported patients with co-occurrence of GBS and PRES. Almost all cases have occurred in women over the age of 55, raising the possibility of increased sensitivity to dysautonomia in this patient group.